Konseptualisasi News Vodcast: Jurnalisme Baru untuk Khalayak Muda - Wiguna, Okta; Famega Syavira Putri; Nur Aziza Sasmi , Nanda Adjeng Castity (Persatuan Wartawan Indonesia, 2025)
Podcasts incorporating video elements are emerging as a strategic content innovation among traditional media outlets, particularly as a means to engage younger audiences. The effectiveness of this format is exemplified by the success of the award-winning Bocor Alus Politik podcast, produced by Tempo. However, this trend presents a new challenge for academic inquiry, as existing conceptualizations of podcasts primarily assume an audio-based format, overlooking the production and consumption dynamics introduced by visual elements. This paper seeks to establish a new conceptual definition of the